Fast-Strain Encoded Cardiac Magnetic Resonance During Vasodilator Perfusion Stress Testing - Steen, Henning; Montenbruck, Moritz; Kelle, Sebastian; Esch, Sebastian; Schwarz, Arne Kristian; Giusca, Sorin; Korosoglou, Grigorios (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac magnetic resonance perfusion imaging during vasodilator stress is an established modality in patients with suspected and known coronary artery disease (CAD). Aim: This study aimed to evaluate the performance of fast-Strain-Encoded-MRI (fast-SENC) for the diagnostic classification and risk stratification of patients with ischemic heart disease. Methods: Perfusion and fast-SENC cardiac magnetic resonance (CMR) images were retrospectively analyzed in 111 patients who underwent stress CMR. The average myocardial perfusion score index, global and segmental longitudinal and circumferential strain (GLS and GCS and SLS and SCS, respectively), were measured at rest and during stress. The combination of SLS and SCS was referred to as segmental aggregate strain (SAS). Segments exhibiting perfusion defects or SAS impairment during stress were defined as “ischemic.” All-cause mortality, non-fatal infarction, and urgent revascularization were deemed as our combined clinical endpoint. Results: During adenosine stress testing, 44 of 111 (39.6%) patients exhibited inducible perfusion abnormalities. During a mean follow-up of 1.94 ± 0.65 years, 25 (22.5%) patients reached the combined endpoint (death in n = 2, infarction in n = 3 and urgent revascularization in n = 20). Inducible perfusion defects were associated with higher number of segments with inducible SAS reduction ≥6.5% (χ2 = 37.8, AUC = 0.79, 95% CI = 0.71–0.87, p < 0.001). In addition, patients with inducible perfusion defects or SAS impairment exhibited poorer outcomes (AUCPerf = 0.81 vs. AUCSAS = 0.74, p = NS vs. each other, and χ2 = 30.8, HR = 10.3 and χ2 = 9.5, HR = 3.5, respectively, p < 0.01 for both). Conclusion: Purely quantitative strain analysis by fast-SENC during vasodilator stress was related to the diagnosis of ischemia by first-pass perfusion and is non-inferior for the risk stratification of patients with ischemic heart disease. This may bear clinical implications, especially in patients with contraindications for contrast agent administration.